Fugitive a novel - Margolin, Phillip (HarperCollins, 2009)
Defense attorney Amanda Jaffe, the heroine of Wild justice and Proof Positive, becomes entrapped in a case of international intrigue and murder that leads her deep into the past ... and into the crosshairs of a killer.